2011
DOI: 10.1007/s11218-011-9163-1
|View full text |Cite
|
Sign up to set email alerts
|

Bullying-victimization problems and aggressive tendencies in Spanish secondary schools students: the role of gender stereotypical traits

Abstract: This paper presents data concerning culturally prescribed gender traits and their influence on bullying/victimization problems and aggressive tendencies from a wide sample of 1,654 Spanish adolescents. The aims of this study were to clarify the effect of masculine traits on male and female secondary students' aggression, and also to explore the role of feminine traits in either the inhibition of aggression or the use of more covert forms. Results show that masculine stereotypical traits are related more strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
2
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 44 publications
5
29
2
16
Order By: Relevance
“…This study, in contrast, found that feminine traits are more related to victimization than are male students [18]. …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study, in contrast, found that feminine traits are more related to victimization than are male students [18]. …”
Section: Discussionmentioning
confidence: 94%
“…Gender differences in the subtypes of bullying play different roles in the pupils’ health [18]. Boys are victims more often when considering different types of bullying as a whole, although differences are not always significant.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, the relation between cyber dating abuse victimization and conformity to gender norms has not yet been explored. Nevertheless, previous studies that have analyzed the relation between conventional gender norms and bullying behaviors have reported that youths not conforming to traditional masculine gender norms were more victimized by their peers [49,50].…”
Section: Gender Norms and Dating Abusementioning
confidence: 93%
“…De modo similar en Granada (España) se desarrolló una investigación que tuvo como objetivo analizar y establecer los índices de Victimización, Bullying y Conducta Violenta y su posible relación con el género, residencia habitual y práctica de Actividad Física de adolescentes de 13 a 17 años, en la que se encontraron diferencias significativas con relación al sexo, los resultados contrastan con la teoría, los hombres son en mayor medida agresores y observadores, en comparación con las mujeres quienes son víctimas con alta frecuencia, aunque lo perciben en menor medida (Ortega Aznar, Ruz, Cortes, & Martínez, 2015). A su vez, las mujeres que acosan a sus compañeros, tienden a usar estrategias indirectas y relacionales, a diferencia de los hombres que usan formas más directas de agresión (Navarro, Larrañaga, & Yubero, 2011;Björkqvist, Lagerspetz, & Kaukiainen, 1992). Por último, no se encontraron diferencias significativas en ambos sexos en cuanto a la agresión verbal (Björkqvist, Österman, & Kaukiainen, 1992)…”
Section: Diferencias De Sexo En La Intimidación Escolarunclassified